Peran Praktik Supply Chain Management (SCM) dalam Meningkatkan Daya Saing Kopi Tanggamus Provinsi Lampung - Nurul Husna; Angga Febrian; Mutiasari Nur Wulan; Irham Lihan (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2022)
Indonesia is one of the coffee exporting countries which occupies the fourth largest position in the world. One of the best coffee producing areas in Indonesia is Lampung Province. Tanggamus is one of the main coffee producing districts of Lampung Province. In 2015 the production of Tanggamus Coffee decreased quite a bit, then in 2016 it increased rapidly, but in 2017 the production declined again until 2018 has not increased rapidly. An effective SCM is possible to gain competitive advantage and increase company production. SCM is an approach to efficiently integrate suppliers, manufacturers, warehouses, and stores to produce and distribute goods in the right quantity, at the right place, and at the right time for the right cost. This study aims to determine the role of SCM practices as measured by three aspects, namely strategic supplier partnership, customer relationship, and information sharing on competitive advantage. Data collection techniques used are field studies through interviews and questionnaires addressed to the Chair, Secretary, and Treasurer of the Coffee Farmers Group who are active in the Beringin Jaya Gapoktan, Sumberejo District, Tanggamus Regency which is the research sample. For data processing using partial least squares (PLS) with SmartPLS software. The results of this study indicate that the practice of SCM has a significant effect on competitive advantage.